Identifying Who Benefits the Most from a Community Health Worker-Led Multicomponent Intervention for Hypertension - Meng Pan; Andrea Beratarrechea; Rosana Poggio; Hua He; Chung-Shiuan Chen; Jing Chen; Vilma Irazola; Adolfo Rubinstein; Jiang He; Katherine T. Mills (International Journal of Hypertension)
Background. Uncontrolled hypertension is a major public health challenge in low- and middle-income countries. The Hypertension Control Program in Argentina (HCPIA) showed that a community health worker-led multicomponent intervention was effective for blood pressure (BP) reduction in resource-limited settings, but whether the intervention was equally effective across participant subgroups is unknown. Objective. To identify participants who benefit the most from the HCPIA BP control intervention. Methods. This secondary analysis used data from HCPIA, a successful 18-month cluster-randomized trial in 18 health centers with 1,432 low-income hypertensive patients in Argentina. Fifteen baseline characteristics were used to define subgroups. The proportion of controlled BP (<140/90 mmHg) was estimated using generalized linear mixed models with arm-by-subgroup interaction terms. The distribution of trial BP response among intervention patient subgroups was assessed. Results. Participants were 53.0% female, a mean age of 56 years, and 17.4% controlled BP at baseline. After the intervention, 72.9% of intervention and 52.2% of control participants had controlled BP. The intervention was more effective in physically inactive patients (OR = 2.76, 95% CI: 1.82 and 4.21; p for interaction = 0.04), moderately active patients (OR = 3.08, 95% CI: 1.90 and 4.99; p for interaction = 0.03), and those with uncontrolled BP at baseline (OR = 2.77, 95% CI: 2.15 and 3.57; p for interaction = 0.05). Among intervention participants, 20.2% had no BP response (BP change < −4 mmHg), 41.3% had a moderate BP response (BP change: −4 mmHg to −24 mmHg), and 38.5% had a high BP response (BP change > −24 mmHg). Women (p=0.01), those who were physically inactive (p=0.03), and those not taking antihypertensive medications at baseline (p=0.001) had the greatest BP response. Conclusion. The effect of the intervention was consistent across many subgroups with some key groups showing a particularly strong intervention effect. These findings could be useful for planning future hypertension control programs in low- and middle-income countries.